A study on ethics in applying prank calls by Hitz FM: The acceptance among undergraduate diploma students from Faculty of Communication and Media Studies in UiTM Negeri Sembilan, Kampus Rembau / Nur Arassh Iqbal Mohammad ... [et al.] - Mohammad, Nur Arassh Iqbal; Mohd Asri, Nurul Assykin; Mohamed Sharidan, Muhd Rabani; Mohd Fuad, Faliqah Alia Radin (2018)
The purpose of this research was to identify the real purposes of Hitz FM conducting prank calls. This research examined the precautions has been taken by Hitz FM to ensure their deejay practice and adhere ethics in conducting prank calls. This research also figured out investigating how does the undergraduate diploma students' acceptance towards the prank calls. Purposive sampling was used in this research to reach a targeted sample quickly. In order to complete this research, researcher conducted an in-depth interview with deejays from Hitz FM. Moreover, the method used was thematic analysis. Data were collected by conducting interview with six informants which were undergraduate diploma students of Communication and Media Studies aged 18-20 from UiTM Negeri Sembilan, Kampus Rembau to reach research objectives.